Role of 5-aminosalicylic acid in ulcerative colitis management in 8 Asian territories: a physician survey - Julajak Limsrivilai; Allen Yu-hung Lai; Silvia T. H. Li; Murdani Abdullah; Raja Affendi Raja Ali; Satimai Aniwan; Hoang Huu Bui; Jen-Wei Chou; Ida Normiha Hilmi; Wee Chian Lim; Jose Sollano; Michelle Mui Hian Teo; et al. (Intestinal Research)
Clinical guidelines typically endorse conventional therapies such as 5-aminosalicylic acid (5-ASA) as the mainstay of ulcerative colitis management. However, the degree of adoption and application of guideline recommendations by physicians within Asia remains unclear. This study aims to understand the prescribing patterns of 5-ASA and implementation of current guideline recommendations across Asian clinical practice. A physician survey was conducted among inflammatory bowel disease specialists in 8 Asian territories to understand practices and preferences in ulcerative colitis management, focusing on the use of 5-ASA and concordance with guideline recommendations. Survey findings were validated by country experts in diverse healthcare settings. Subgroup analyses stratified data by income levels and treatment reimbursement status. Ninety-eight valid responses were received from inflammatory bowel disease specialists or gastroenterologists among 8 economic entities. Significant differences were found in clinical practices and treatment preferences for ulcerative colitis management among different income-level and government-subsidy groups. Survey results are summarized in 8 findings that illustrate trends in 5-ASA use and guideline implementation across Asian territories. This study emphasizes socioeconomic factors that impact the adoption of guideline recommendations in real-world practice. Our findings indicate an eclectic approach to guideline implementation across Asia, based on resource availability and feasibility of treatment goals.